A Bibliometric Analysis of Global Research on the Psychological Burden of HIV Stigma Among Adults: Implications for Nursing Practice - Wilandika, Angga; Sari, Diah Nur Indah (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: HIV-related stigma remains a persistent barrier to psychological well-being and care among people living with HIV. Although research on its psychological burden has grown, no bibliometric synthesis has mapped its development or implications for nursing practice.Purpose: This study aimed to conduct a bibliometric analysis of global research on the psychological burden of HIV stigma among adults, with particular attention to thematic evolution and implications for nursing care.Methods: A bibliometric and thematic analysis was conducted on 131 journal articles indexed in Scopus from 2014 to 2025. Bibliometric mapping was performed using VOSviewer to examine publication trends, authorship patterns, country distribution, keyword co-occurrence networks, and temporal thematic evolution.Results: The analysis found no publications prior to 2014, with output peaking in 2022 and 2024, confirming the field’s novelty. Keyword clustering revealed six thematic domains: psychological distress (depression, anxiety, shame), treatment adherence and healthcare engagement, trauma-related stigma, resilience and protective factors, methodological advances in stigma measurement, and structural-societal stigma. Temporal analysis indicated a shift from documenting emotional distress to examining mediating processes, resilience, and intersectionality, marking a transition from descriptive to explanatory and intervention-focused research.Conclusion: Research on the psychological burden of HIV stigma has expanded, with depression and anxiety remaining central, but increasing attention to resilience, coping, and systemic factors. However, gaps persist in translating these insights into stigma-sensitive nursing interventions. This bibliometric synthesis provides evidence to inform nurse-led strategies such as therapeutic communication, psychoeducation, and psychosocial support to mitigate stigma’s psychological impact on PLHIV.